2019
DOI: 10.5194/nhess-19-389-2019
|View full text |Cite
|
Sign up to set email alerts
|

Estimations of rip current rescues and drowning in the United States

Abstract: Abstract. Rip currents are the greatest hazard to swimmers on surf beaches, but due to a lack of consistent incident reporting in many countries, it is often difficult to quantify the number of rip-current-related rescues and drowning deaths occurring along surf beaches. This study examines this problem using rescue data reported to the United States Lifesaving Association (USLA) by surf beach rescuers from 1997 through 2016. These data were checked, corrected, and culled so that only data from surf beach resc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…However, several studies have shown that even when people are aware of what rip currents are and why they are dangerous, they are largely unable to visually identify a rip current in a photograph. Caldwell et al (2013) report the successful identification of channel rips to be lower than 20 %, with success rates of up to 40 % reported by Willcox-Pidgeon et al (2017) and a 48 % success rate in selecting a safe place to swim reported by Sherker et al (2010). A similar study by Surf Life Saving Australia (SLSA, 2019a) surveyed ocean swimmers who self-assessed as highly competent and reported that only 27 % were able to accurately identify rip currents in multiple photographs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown that even when people are aware of what rip currents are and why they are dangerous, they are largely unable to visually identify a rip current in a photograph. Caldwell et al (2013) report the successful identification of channel rips to be lower than 20 %, with success rates of up to 40 % reported by Willcox-Pidgeon et al (2017) and a 48 % success rate in selecting a safe place to swim reported by Sherker et al (2010). A similar study by Surf Life Saving Australia (SLSA, 2019a) surveyed ocean swimmers who self-assessed as highly competent and reported that only 27 % were able to accurately identify rip currents in multiple photographs.…”
Section: Introductionmentioning
confidence: 99%
“…The calm, smooth visual signature associated with channel rips is particularly important in terms of educating people about how to identify the hazard as inexperienced or uninformed beach users will often pick this calmer patch of water as the safest place to swim to avoid the breaking waves either side of the rip which are perceived as being more dangerous (Caldwell et al, 2013). Rip current visual signatures also vary as morphology, tidal stage, or wave energy changes (Pitman et al, 2016), meaning an observer might have to rely on different visual signatures for the same rip channel at different times during the day.…”
Section: Introductionmentioning
confidence: 99%
“…As the rips could carry the victims to the middle of the sea, they are typically associated with drowning cases. United States Lifesaving Association (USLA) projected that more than 100 rip current fatalities have occurred annually in the USA (Brewster et al 2019 ). More people in Australia die from rip currents compared to other threats such as floods, shark attacks, and bushfires (Brander et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rip currents are the main hazard to recreational swimmers and bathers and, in recent years, have been recognized as a serious global public health issue Woodward et al, 2013;Kumar and Prasad, 2014;Arozarena et al, 2015;Brewster et al, 2019;Vlodarchyk et al, 2019). Rips are strong, seaward-directed currents that can develop on beaches characterized by wave breaking within the surf zone (Castelle et al, 2016) and are capable of transporting swimmers a significant distance away from the shoreline into deeper waters.…”
Section: Introductionmentioning
confidence: 99%
“…Weak swimmers or those who try and fight the current can become stressed and experience panic (Brander et al, 2011;Drozdzewski et al, 2012), leading to increased adrenaline, an elevated heart rate and blood pressure, and rapid and shallow breathing. On recreational beaches in Australia and the US, rips have been identified as the main cause of drownings and are believed to be responsible for nearly 80 % of all rescues Brewster et al, 2019). It is estimated that the annual number of rip current drownings exceeds the number of fatalities caused by hurricanes, forest fires, and floods in Australia , while rip-related drownings on a relatively small number of beaches in Costa Rica account for a disproportionately large number of violent deaths in the country (Arozarena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%